Microstructure Analysis of Ti–6Al–4V Alloy with TBC after Cyclic Oxidation for Aerospace Applications - Takahashi, Renata Jesuina; Fazan, Leonardo Henrique; Baldan, Renato [UNESP]; Reis, Danieli Aparecida Pereira (FapUNIFESP (SciELO), 2025)
The application of thermal barrier coatings (TBC) on titanium alloys has been widely used in aircraft turbines to maintain their properties such as low density, mechanical strength, while also enabling higher operational temperatures and thermal efficiency. Corrosion and hot oxidation damage the TBC, which consist of a metallic substrate, a metallic coating (bond coat, BC), a thermally grown oxide (TGO), and a ceramic topcoat. This study assessed the oxidation behavior of Ti-6Al-4V with and without BC and TBC. Oxidation tests were conducted cyclically in air at temperatures of 500, 600, and 800 °C in an automatic furnace, in which each cycle consisted of 60 minutes at the target temperature followed by 10 minutes at room temperature. After 100 thermal cycles, the samples were analyzed using scanning electron microscopy (SEM), optical microscopy (OM), and X-ray diffraction (XRD). With increasing temperature, the uncoated Ti-6Al-4V alloy showed the formation of titanium oxides on the surface and an approximate 20% increase in grain size. In contrast, the TBC system demonstrated greater durability under high temperature conditions and showed no evidence of delamination.